2013
DOI: 10.1111/nan.12020
|View full text |Cite
|
Sign up to set email alerts
|

Review: The role of vitamin D in nervous system health and disease

Abstract: Vitamin D and its metabolites have pleomorphic roles in both nervous system health and disease. Animal models have been paramount in contributing to our knowledge and understanding of the consequences of vitamin D deficiency on brain development and its implications for adult psychiatric and neurological diseases. The conflation of in vitro, ex vivo, and animal model data provide compelling evidence that vitamin D has a crucial role in proliferation, differentiation, neurotrophism, neuroprotection, neurotransm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
266
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(274 citation statements)
references
References 236 publications
(271 reference statements)
1
266
0
7
Order By: Relevance
“…It binds to the vitamin D receptor (VDR) which is found in most parts of the body, including the immune system (Fernandes de Abreu et al, 2009) and the central nervous system (Stumpf, 2012). Vitamin D is involved in the proliferation, differentiation and growth of neurons and has an important role in neuroplasticity (Deluca et al, 2013) both in the developing and adult brain.…”
Section: Introductionmentioning
confidence: 99%
“…It binds to the vitamin D receptor (VDR) which is found in most parts of the body, including the immune system (Fernandes de Abreu et al, 2009) and the central nervous system (Stumpf, 2012). Vitamin D is involved in the proliferation, differentiation and growth of neurons and has an important role in neuroplasticity (Deluca et al, 2013) both in the developing and adult brain.…”
Section: Introductionmentioning
confidence: 99%
“…Latitude, season, cultural norms, religious practices, low awareness, low knowledge/health literacy, indoor lifestyles, urban living, skin pigmentation, malnutrition, diet, co-morbidities like tuberculosis, and drugs may contribute to vitamin D deficiency especially in the in the developing world, moreover, blacks tend to have lower levels of 25(OH)D compared to whites [2,3]. It has been widely demonstrated that Vitamin D is also involved in different non-skeletal functions, including hypertension, diabetes, multiple sclerosis, Alzheimer's disease, Parkinson's disease, and Stroke [4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…While 25-hydroxy vitamin D is viewed as the barometer of vitamin D status, activated 1,25-dihydroxyvitamin D holds a much greater affinity for the vitamin D receptor and is therefore much more effective at eliciting its desired target responses [23]. Interestingly, activated vitamin D is capable of crossing the blood-brain barrier in order to interact with neurons and cells within the nervous system [24,25]. Vitamin D receptors have been located in high concentrations within the mid-brain and brainstem structures that house the preganglionic nerves of the ANS [24].…”
mentioning
confidence: 99%
“…Vitamin D receptors have been located in high concentrations within the mid-brain and brainstem structures that house the preganglionic nerves of the ANS [24]. Neuronal cells with exposure to high concentrations of 1,25-dihydroxy vitamin D have been shown to better regulate the transcription, production, and release of neurotransmitters which act to regulate signal transduction between the ANS and the heart, among other organs [24,25]. From a biological standpoint, there is a clear indication that activated vitamin D could directly interact with the ANS to elicit changes in sympathetic and parasympathetic signaling.…”
mentioning
confidence: 99%